THE EFFECT OF HISTAMINE H1 RECEPTOR ANTAGONISTS ON THE MORPHINE-INDUCED ANTINOCICEPTION IN THE ACUTE TRIGEMINAL MODEL OF NOCICEPTION IN RATS - Khalilzadeh, Emad; Azarpey, Farzin; Hazrati, Reza (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In this study, the effect of different classes of histamine H receptor antagonists (chlorpheniramine, cetirizine, and fexofenadine), µ opioid receptor agonist (morphine), and opioid receptor antagonist (naloxone) in separate and combined treatments were investigated on the acute trigeminal model of pain in rats. 1 Methods: Eye wiping test used for induction of acute trigeminal pain by putting a drop of NaCl, 5 M solution (40 µl) on the corneal surface of the eye, and the number of eye wipes counted during the first 30 seconds. Results: Intraperitoneal injection of both chlorpheniramine and cetirizine at doses of 10 and 20 mg/kg significantly inhibited the acute trigeminal pain. However, fexofenadine did not change corneal pain response. Morphine at doses of 1.25, 2.5, and 5 mg/kg reduced eye wipe responses. Administration of both chlorpheniramine and cetirizine but not fexofenadine before morphine-enhanced morphine analgesic activity, also pretreatment of animals with naloxone inhibited morphine, chlorpheniramine, and cetirizine-induced analgesia in the acute corneal pain. Conclusion: Our results showed that chlorpheniramine as a histamine H antagonist that efficiently Penetrates blood-brain barrier (BBB) and cetirizine with less penetration of BBB but not fexofenadine (an H11 receptor antagonist with a negligible brain-accessibility) could induce analgesia in the acute corneal pain via opioidergic mechanism. Coadministration of morphine with chlorpheniramine or cetirizine could enhance its analgesic activity in the acute trigeminal model of pain in rats. Keywords: Trigeminal pain, Morphine, Histamine H1 receptor antagonists, Naloxone, Rats. <!--[endif]--><!--[if !mso]--> <!--[endif]--> 1 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]> <v:shape id="_x0000_s1028" type="#_x0000_t202" style='position:absolute; left:0;text-align:left;margin-left:291.6pt;margin-top:8.35pt;width:2.6pt; height:4.65pt;z-index:-4;mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->Objective:Inthisstudy,theeffectofdifferentclassesofhistamineH receptorantagonists(chlorpheniramine,cetirizine,andfexofenadine),µ <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> opioid receptoragonist (morphine), and opioid receptorantagonist (naloxone)in separate and combinedtreatments were investigatedon the acute trigeminal model of pain in rats. Methods:Eyewiping testusedforinductionofacutetrigeminalpainbyputtingadropofNaCl,5Msolution(40µl)onthecornealsurfaceoftheeye, and the number of eye wipes counted during the first 30 seconds. Results:Intraperitonealinjectionofbothchlorpheniramineandcetirizineatdosesof10and20mg/kgsignificantlyinhibitedtheacutetrigeminalpain. However,fexofenadinedidnotchangecornealpainresponse.Morphineatdosesof1.25,2.5,and5mg/kgreducedeyewiperesponses.Administration of both chlorpheniramine and cetirizine but not fexofenadine before morphine-enhanced morphine analgesic activity, also pretreatment of animals with naloxone inhibited morphine, chlorpheniramine, and cetirizine-induced analgesia in the acute corneal pain. <span style="font-size: 8.0pt; line-height: 100%; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <!--[endif]--><!--[if !mso]--> <!--[endif]--> 1 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]><v:shape id="_x0000_s1031" type="#_x0000_t202" style='position:absolute;left:0; text-align:left;margin-left:304.5pt;margin-top:7pt;width:2.6pt;height:4.65pt; z-index:-1;mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->Conclusion:OurresultsshowedthatchlorpheniramineasahistamineH antagonistthatefficientlyPenetratesblood-brainbarrier(BBB)and <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <!--[endif]--><!--[if !mso]--> <!--[endif]--> 1 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]><v:shape id="_x0000_s1029" type="#_x0000_t202" style='position:absolute;left:0;text-align:left;margin-left:271.7pt; margin-top:7.1pt;width:2.6pt;height:4.65pt;z-index:-3; mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->cetirizinewithlesspenetrationofBBBbutnotfexofenadine(anH receptorantagonistwithanegligiblebrain-accessibility)couldinduceanalgesia in the acute corneal pain via opioidergic mechanism. Coadministration of morphine with chlorpheniramine or cetirizine could enhance its analgesic activity in the acute trigeminal model of pain in rats. <!--[if gte vml 1]><v:group id="_x0000_s1026" style='position:absolute;left:0;text-align:left; margin-left:45.65pt;margin-top:14.35pt;width:504.15pt;height:0;z-index:-5; mso-position-horizontal-relative:page' coordorigin="913,287" coordsize="10083,0"> <![endif]--><!--[if !vml]--> <!--[endif]--><!--[if gte vml 1]><v:shape id="_x0000_s1030" type="#_x0000_t202" style='position:absolute;left:0; text-align:left;margin-left:222.75pt;margin-top:7pt;width:2.6pt;height:4.65pt; z-index:-2;mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--> <!--[endif]--><!--[if !mso]--> <!--[endif]--> 1 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[endif]-->Keywords: Trigeminal pain, Morphine, Histamine H receptor antagonists, Naloxone, Rats.